Policies to Protect Healthcare Providers in Public Hospitals in Egypt Amid the First Wave Covid-19 Crisis: A Case Study - Sayed, Moushira Hosny Ezzelarab (AUC Knowledge Fountain, 2022)
The emergence of coronavirus disease 2019 (COVID-19) pandemic in 2020 became a main public health problem among the worlds. Universally, healthcare workers were forced to face an unprecedented challenge since the outbreak COVID-19. The World Health Organization (WHO) has been trying to reduce transmission of COVID-19 between different countries by setting regulations and standards in attempt to control the transmission of infection. The protection of healthcare workers working as frontline workers for COVID-19 is a priority. To assess the occupational workplace policies to protect healthcare workers in public university hospitals in Egypt during the first wave of COVID-19, this research was conducted at a major public university hospital. These policies were crucial to protect the frontline workers from COVID-19 infection amid the first wave of COVID-19. In depth interviews were conducted to gather information about the current policies in the case study hospital. Results of this research are vital to all public hospitals which provide service a large segment of the population in Egypt. Defective implementation of the workplace policies, lack of needed managerial support, and poor communication between the administration and the healthcare workers were highlighted. The challenge of substandard infrastructure and insufficient resources in the healthcare system during the pandemic at the case study contributed to the crisis. Additionally, the absence of psychological and mental health support needed to health care workers amid the ongoing stress of COVID-19 with all the mental challenges they are facing. The findings of this research give insights to the protective workplace policies of COVID-19 for healthcare workers at the case study public hospitals and challenges in their application and different policy alternatives.